Neurostomatological Syndromes in Patients with Psychosomatic Disorders (Psychopathological Syndromes) (lecture) - Zozulia, Іван; Volosovets, Антон; Volosovets, Тетяна; Doroshenko, Олена; Trostyansky, Ярослав (Actual Dentistry, 2026)
The large-scale war of the Russian Federation against Ukraine has resulted not only in physical disabilities among both military personnel and civilians (injuries, burns, poisoning, etc.), but also in the development or exacerbation of mental health disorders such as panic attacks, neuroses, and hysteria. These conditions arise under severe stress and manifest through functional disturbances of mental health and pain syndromes. We examined a cohort of 145 patients aged 30–58 years who developed mental health disorders in the context of massive stress. Twenty-five of them had pre-existing neurotic manifestations that had been compensated by medication; however, stress associated with hostilities reactivated these disturbances and significantly aggravated their condition. Clinical examinations were performed by dentists, neurologists, cardiologists, and otolaryngologists (when required). Additional diagnostic procedures included CT, MRI, ultrasound, ECG, and dental radiography. Laboratory investigations comprised blood glucose, cholesterol and lipoprotein levels, biochemical blood tests, and coagulation profiles. These examinations allowed us to exclude organic lesions of the brain and internal organs and to confirm mental health disturbances. Furthermore, inpatient assessments using international diagnostic scales were conducted to validate the diagnoses. Mental health disorders may present as anxiety, panic attacks, depression, delirium, psychosis, neurasthenia, hysteria, obsessive-compulsive disorder, and other conditions, which can be acute or chronic. Such disorders may occur in association with neurological and somatic diseases (cardiovascular, cerebrovascular, or internal organ pathology). Therefore, the task of internists, family physicians, neurologists, cardiologists, and dentists is to collect a thorough medical, life, and allergy history, review previous treatment methods, and develop a comprehensive management plan at both pre-hospital and hospital stages.